Stability and stabilization of 2-D Roesser systems with time-varying delays subject to missing measurements. (April 2018) - Xuhui, Bu; Senping, Tian; Lizhi, Cui; Junqi, Yang
This paper addresses the problem of stability and stabilization for a class of two-dimensional (2-D) Roesser systems with time-varying delays subject to missing measurements. The missing phenomenon of the sensor measurement is governed by a stochastic variable satisfying the Bernoulli random binary distribution. The aim of this paper is focused on the design of a state feedback controller such that the closed-loop 2-D system is asymptotic stability in the mean square sense. A delay-dependent stability condition is derived in terms of linear matrix inequalities, and formulas can be given for the control law design. Furthermore, the results are also extended to robust stability and stabilization of the uncertain 2-D time-varying delayed system. Numerical examples are given to illustrate the effectiveness of proposed approach.